The 6-month drug survival rate in patients withrheumatoid arthritis treated with tofacitinib - Karataş, Ahmet; Gür, Mustaf; Öz, Burak; Sağır, Rabia Pişkin; Hohluoğlu, Abdulvahap; Gozel, Nevzat; Koca, Suleyman Serdar (My University, 2021)
Aim: Rheumatoid arthritis (RA) is a progressive, inflammatory, autoimmune disease that particularly affects the joints. Tofacitinib is the first oral Janus kinase inhibitor approved for RA treatment. We aimed to analyze the 6-month drug survival rate and factors affecting the discontinuation of tofacitinib in RA patients.Materials and Methods: Age, gender, rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) levels, whether to continue treatment tofacitinib, if treatment is not continued what treatment is applied, use of biological agent before tofacitinib treatment were retrospectively recorded from the patient data.Results: 30 RA patients included in the study (29 female, 1 male) with a mean age of 50.5 ± 11.3 years. At the 6th month of treatment of tofacitinib, the drug survival rates were 50%. There was no significant difference between CCP positive and negative patients as well as between RF positive and negative patients in terms of drug survival rates (p = 0.92 and p = 0.90, respectively). The drug survival rates were alike in tofacitinib monotherapy and combined therapy of tofacitinib with any conventional DMARD (p = 0.36). The tofacitinib survival rates were similar in biologically naïve patients and in patients who had received at least one previous biological DMARD (p = 0.70).Conclusion: Half of the RA patients receiving tofacitinib treatment continue their treatment at the 6th month. The drug survival rate was not associated with co-treatment with conventional DMARD, auto-antibody positivities, and previously used biological DMARD therapy. These findings support that tofacitinib shows similar efficacy when used as combined or monotherapy, in seronegative or seropositive patients, and in biologic resistant or naive patients.
Keywords: Romatoloji; İmmünoloji